Новая конструкция светодиодного светильника с тепловыми трубами - Pekur, Demyd; Nikolaenko, Yurii; Sorokin, Viktor (PE "Politekhperiodika", Book and Journal Publishers, 2019)
The problem of climate change poses a challenge for humanity: it is necessary to reduce harmful emissions into the atmosphere, caused mainly by the burning of coal in thermal power plants. Partially, this problem can be solved by the use of energy-saving devices and equipment, including the replacement of traditional light sources with more efficient LEDs. This, however, causes the problem of ensuring normal thermal modes of the LEDs, since the more powerfull the LED is, the more heat is released in their semiconductor crystals, which leads to an increase in the temperature of the crystals and a decrease in the reliability of the device. This problem becomes especially urgent when using powerful multi-chip LED light sources, the so-called SOB matrices, whose power even now exceeds 500 W.This article presents a new design of a powerful LED lamp for indoor illumination of rooms with low ceilings. The heat from the LED is transferred via heat pipes to the heat exchanger rings looped around the light source. The heat exchanger rings are cooled by the natural convection of the surrounding air (at an ambient air temperature of 20°C). Computer simulation allowed evaluating the ability of the proposed cooling system to provide a normal thermal mode of the LED light source. The results on the computer simulations of the temperature field of light source's cooling system showed that when the LED power is 300 W, the temperature of the light source's base at the point where it is connected to the light source does not exceed 67.6°C. When the contact zone is covered with a 0.1 mm layer of heat-conducting paste (Arctic Silver 5 type) with a thermal conductivity coefficient of 8.7 W/(m·°C), the temperature of the LED case reaches 70°C. If the thermal resistance of the LED light source is 0.1°C/W, then the temperature of its semiconductor crystals will be 100°C, well below the allowable temperature value of 150°C. The total thermal resistance of the cooling system is 0.159°C/W.